The Mediating Role of Work Stress between Work-Family Conflict and Work-Life Balance on Female Bank Employees - Kusumawardani, Samitha Tariz; Rini, Hesty Prima (LPPM Universitas Trunojoyo Madura, 2024)
Finding an harmonious balance between work and personal life is a challenge for company management but also a competitive potential. This study investigates the effects of work-family conflict on work-life balance is mediated by work stress as an intervening variable in permanent and married female employees at BRI Kuta Branch. Conducted with a quantitative approach, this study involved 51 respondents using saturation sampling to determine the sample. The data in this research was gathered by a questionnaire and examined using SEM-PLS method with the assistance of Smart-PLS software. The findings proved that there is a negative and significant effect of work-family conflict on work-life balance. Furthermore, Work stress is able to mediate work-family conflicts that have a negative and significant effect on work-life balance of female employees of PT Bank Rakyat Indonesia (BRI) Kuta Branch.